Organizational Culture and Organizational Commitment: A Qualitative Case Study in a Private University Faculty Setting - Rafika Rahmawati; Adham Adham; Purnama Putra (SAN Scientific, 2026)
This study aims to analyze the implementation of organizational culture and its impact on employees’ organizational commitment within a faculty at a private university. A qualitative case study approach was employed, involving 15 participants consisting of lecturers and administrative staff selected through purposive sampling based on tenure and organizational involvement. Data was collected through semi-structured interviews, direct observations, and document analysis, with an interview protocol focusing on cultural practices, communication patterns, and perceived commitment levels. Data was analyzed using thematic coding, including open, axial, and selective coding to identify key patterns and relationships. To ensure research rigor, credibility strategies such as data triangulation across sources and member checking were applied to validate findings. The results indicate that organizational culture, characterized by collaboration, discipline, transparency, and open communication, significantly strengthens affective, normative, and continuance commitment. A supportive work environment fosters emotional attachment, while clear policies and professional development opportunities enhance employees' sense of responsibility and intention to remain in the organization. These findings provide both theoretical and practical implications for strengthening organizational commitment in higher education institutions.